2019
DOI: 10.1002/adfm.201804433
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Raman Spectroscopy for Assessing Anisotropic Strain in Thin Films of Doped Ceria

Abstract: A protocol for characterizing relaxation of anisotropic strain in thin films of 10 mol% Eu-or Sm-doped ceria is described. The method is based on comparison of Raman spectra and X-ray diffraction patterns from substratesupported films, displaying in-plane compressive strain (initial state), with analogous data from 2 mm diameter self-supported films (i.e., membranes), prepared by partial substrate removal (final state). These membranes are found to be relaxed, i.e., approximately unstrained, but with increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 33 publications
5
33
0
Order By: Relevance
“…Kraynis et al studied the Grüneisen parameter of Eu 3+ and Sm 3+ -doped ceria thin films under biaxial strain relaxation. 209 Similar to the trivalent doping effect discussed above, a value of 0.4-0.6 was found for the equivalent Grüneisen parameter. Gopal et al showed that biaxial strain, whether compressive and tensile, increases the reducibility of CeO 2 thin films.…”
Section: Investigation Of Ceria Defect-chemistry By Raman Spectroscopsupporting
confidence: 58%
See 3 more Smart Citations
“…Kraynis et al studied the Grüneisen parameter of Eu 3+ and Sm 3+ -doped ceria thin films under biaxial strain relaxation. 209 Similar to the trivalent doping effect discussed above, a value of 0.4-0.6 was found for the equivalent Grüneisen parameter. Gopal et al showed that biaxial strain, whether compressive and tensile, increases the reducibility of CeO 2 thin films.…”
Section: Investigation Of Ceria Defect-chemistry By Raman Spectroscopsupporting
confidence: 58%
“…Even though an effect of anisotropic strain on Raman shifts of ceria films was reported by various authors, 26,201,209,212 the effect of strain on vibrational lattice dynamics -and thereby Grüneisen parameters remains only partly understood. Iguchi et al 207 suggested that since films of ceria and doped ceria experience anisotropic stress conditions, the Grüneisen relation as derived from high pressure experiments has to be modified for the biaxial modulus.…”
Section: The Effect Of Anisotropic Strain On Raman Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…Etching a well in the Si substrate produces 2 mm diameter, tethered, circular membranes. Since even after annealing, the sputtered film stack retains residual in‐plane, compressive strain (0.3–0.8%), [ 17 ] the tethered membrane buckles upon substrate removal with buckling depth ≈70 µm (Figure 1d). The membrane thus assumes the shape of a “soup‐bowl” with an almost flat, circular base, ≈1 mm in diameter, surrounded by a petal‐like, wrinkled periphery (see Section S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%